There Is an Alternative: With Herbert Marcuse and Mark Fisher Towards a Political Aesthetics of Neoliberalism - Schutzbach, Lukas (J.B. Metzler, 2023)
Introduction -- Neoliberalism and One-Dimensional Society -- One-Dimensional Society and Emancipatory Art -- Emancipatory Art and Neoliberalism in Ben Lerner's 10:04 -- Conclusions.
Überarbeitete und erweiterte Version der Dissertation im Bereich English studies
Keywords: Hochschulschrift; Poetik; Neoliberalismus